A 7 Cs model of effective service leadership. Issue 6 (6th August 2018) - Zou, Tracy X.P.; Snell, Robin S.; Y.L. Chan, Maureen; Wong, Amy L.Y.
Abstract : Purpose: The purpose of this paper is to identify attributes and practices that are salient for effectiveness in middle- and senior-level service leadership positions. Design/methodology/approach: Critical incident interviews were conducted with 17 key informants, who were service leaders in various service sectors in Hong Kong, and with ten stakeholders. Findings: Grounded theory analysis generated a 7 Cs model with seven categories of service leadership attributes and practices: character, choreography, care, creativity, charisma, collaborating and competence self-improvement, and 24 constituent concepts. There was concordance between pairs of key informants and stakeholders. Research limitations/implications: Further research could investigate the impact on frontline service leaders' performance if one or more of the 7 Cs are perceived to be absent or deficient among leaders at more senior levels, and whether there are acceptable substitutes for particular Cs. Practical implications: The 7 Cs model identifies service leadership attributes and practices across diverse sectors. Originality/value: The 7 Cs model provides a map for orienting the developmental preparation of individuals, who are aspiring to become middle- and senior-level leaders in economies that have become highly dependent on service.